Social Relations between Muslim and Christian Communities: A Study of Living Hadith in Rejoagung Village Jember Regency - Kasman Kasman; Makhrus Makhrus; Achmadana Syachrizal M. F. (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2024)
Abstract: The relationship between Islam and Christianity in Indonesia is often marked by religious conflicts due to a lack of understanding of the fundamental teachings of moderation in both religions. In Rejoagung, a village with a predominantly Protestant Christian population bound by traditional customs, the relationship between the Muslim and Christian communities has distinct origins: Christians through migration and Muslims through marriage. This study aims to examine the lives of the Muslim minority in Rejoagung, focusing on the background of community formation and existing socio-religious relations. Utilizing a qualitative approach and phenomenological method, this research reveals the lived experiences of the Muslim minority in Rejoagung through interviews, observations, and documentation. The findings indicate that values of mutual cooperation and humanity are the foundation for interfaith harmony. While there are social interactions such as visiting each other during religious celebrations and interfaith marriages, there remains controversy over Muslim participation in other religious rituals, which Muslim scholars unanimously deem impermissible. In the context of Muslim and Christian relations in Rejoagung, two pertinent hadiths are prevalent: the hadith concerning marriage between Muslims and Alh al-Kitab, and the hadith regarding Muslim involvement in the worship practices of other faiths. These findings demonstrate that despite the strict principles in Islamic teachings regarding certain boundaries, values of humanity and mutual cooperation play a crucial role in fostering and maintaining interfaith harmony in Rejoagung.